The scales applied in the melody of Oscar Peterson's jazz piano improvisation of 'Blues Etude' / Nur Ashikin Anwar. - Anwar, Nur Ashikin (2020)
Learning to improvise jazz requires a methodical approach. One might learn how a jazz master plays and use that knowledge to find ones own voice. Oscar Peterson is a jazz piano master we should learn from. This thesis studied the transcription of his own composition Blues Etude and identified the scales applied in the melody, and analyzed how the scales are applied. There are 19 different scales that have been identified in 17 choruses and their location mapped out in a table. The scales were ranked according to the frequency of use. How the scales are used is as follows, 1.) the scales follow a target tone, 2.) we can choose certain scale degrees to make a unique scale pattern and repeat it, 3.) the scales can be connected to each other.using a chromatic connecting material, 4.) the scales can be used to mark chord changes, and finally, 5.) Scale patterns can be^in and end with the same pitch. As a recommendation, the practice of scales should include playing with jazz rhythms in order to produce authentic jazz sound.